The Anti-Inflammatory Effect of Nanoarchaeosomes on Human Endothelial Cells - Nancy Charó; Horacio Jerez; Silvio Tatti; Eder Lilia Romero; Mirta Schattner (MDPI AG, 2022)
Archaebacterias are considered a unique source of novel biomaterials of interest for nanomedicine. In this perspective, the effects of nanoarchaeosomes (ARC), which are nanovesicles prepared from polar lipids extracted from the extreme halophilic Halorubrum tebenquinchense, on human umbilical vein endothelial cells (HUVEC) were investigated in physiological and under inflammatory static conditions. Upon incubation, ARC (170 nm mean size, −41 mV ζ) did not affect viability, cell proliferation, and expression of intercellular adhesion molecule-1 (ICAM-1) and E-selectin under basal conditions, but reduced expression of both molecules and secretion of IL-6 induced by lypopolysaccharide (LPS), Pam3CSK4 or Escherichia coli. Such effects were not observed with TNF-α or IL-1β stimulation. Interestingly, ARC significantly decreased basal levels of von Willebrand factor (vWF) and levels induced by all stimuli. None of these parameters was altered by liposomes of hydrogenated phosphatidylcholine and cholesterol of comparable size and concentration. Only ARC were endocytosed by HUVEC and reduced mRNA expression of ICAM-1 and vWF via NF-ĸB and ERK1/2 in LPS-stimulated cells. This is the first report of the anti-inflammatory effect of ARC on endothelial cells and our data suggest that its future use in vascular disease may hopefully be of particular interest.